Case Report: Suspected Thiamphenicol-Induced Stevens-Johnshon Syndrome-Toxic Epidermal Necrolisis Overlap in A Child – Diagnosis and Management - Ika Diamanda Apriano; Deryne Anggia Paramita; Kristo Alberto Nababan (Indonesian Journal of Global Health Research, 2025)
Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are rare delayed-type hypersensitivity reactions characterized by detachment of the epidermis and mucous membranes, along with skin necrosis. While these conditions are rare in children, they are most commonly caused by antibiotics, antiepileptic drugs, and antipyretic drugs. This case report aims to highlight thiamphenicol as a rare and potentially overlooked cause of SJS/TEN in pediatric patients. A 14-year-old girl who developed painful red patches accompanied by fluid-filled blisters on almost her entire body which appeared five days after taking the antibiotic thiamphenicol. The patient also experienced red, watery eyes; blisters on the lips and oral cavity; involvement of the nipples; and was unable to swallow due to severe pain in the mouth and throat. The patient was diagnosed with SJS-TEN overlap, and showed a good response to systemic corticosteroids (methilprednisolone) and supportive therapy. Her overall prognosis was favorable, with a Severity-of-Illness Score for Toxic Epidermal Necrolysis (SCORTEN) score of 1. The management of SJS/TEN involves a multidisciplinary specialist approach, immediate withdrawal of the suspected drug, administration of corticosteroids, and comprehensive supportive care.